Cost-effectiveness of uncultivated field-margins and semi-natural patches in Mediterranean areas: A multi-taxa, landscape scale approach. (December 2019) - Segre, Hila; Carmel, Yohay; Segoli, Michal; Tchetchik, Anat; Renan, Ittai; Perevolotsky, Avi; Rotem, Dotan; Shwartz, Assaf
Graphical abstract: Abstract: Careful consideration of the cost-effectiveness of wildlife-friendly practices is key to promote fit-for-purpose agro-ecological policies, but quantitative evaluations of economic costs and ecological benefits compared to other land management alternatives are scarce. We compared the cost-effectiveness of uncultivated field-margins, a widespread wildlife-friendly practice, to that of conserving large semi-natural patches at the landscape scale and over multiple seasons for six crop types in Mediterranean Israel. Increased production expenditures and revenue loss were used to assess costs. Ecological benefits were measured in terms of (1) potential biological pest-control, and (2) richness and abundance of plants, birds, butterflies, ground-dwelling and plant-associated arthropods. Field-margins increased biodiversity by 64 % compared to cultivated land and accounted for 78 % of the biodiversity recorded in semi-natural patches. The biodiversity benefits of field-margins varied across seasons and taxa. Arthropod richness in field-margins did not differ from semi-natural patches, but bird and plant richness were 42–46 % lower. Field-margins increased potential biological pest-control, but with no spillover into the fields. Field-margins were associated with revenue loss in most crop types, leading to lower cost-effectiveness compared to creating large semi-natural patches. Yet, in a few crop types which exhibited low or positive effect of field-margins on income, field-margins were more cost-effective than semi-natural patches. These results indicate that there is no one-size-fits-all agri-environmental policy. Measures need to be locally tailored (e.g. crop-specific) to maximize ecological and economic benefits at large spatial scales, while considering that in many cases setting aside contiguous areas for conservation is more cost-effective than field-scale wildlife-friendly practices.